Experimental implementation of a passive imaging sensor at 94 GHz. Issue 7 (October 2016) - Angelini, Mauro; Frasca, Marco; Rossi, Massimiliano
Abstract This paper describes the design and realization of a W-band radiometric sensor and its imaging performance obtained during indoor and outdoor experimental trials. The system has been used both in indoor and in outdoor scenarios in near-radiative and far-field conditions, respectively.